Implementation of Criminal Sanctions Against Perpetrators of Child Narcotics Abuse - Imah Kardita; Johana Melisa Tobing; Jesika Fatma Sari; Salsa Deviana Puspita Sari (Syntax Idea)
Drug abuse by children is a deviation of behavior or unlawful acts. In the Child Protection Law and the Juvenile Criminal Justice System Law, legal protection must be provided to children who are in conflict with the law. The purpose of this study is to analyze how the implementation of criminal sanctions against perpetrators of drug abuse in children. This research uses the theory of liberalism on the basis of freedom and human rights (HAM). As a vulnerable party in the criminal justice process, even though undergoing the judicial process, children must still receive protection. Based on the interview between the author and the investigator, it can be concluded that all legal processes of convicted drug convicts in children have been running with applicable legal provisions, it's just that there is one thing that should be an important point that is needed during the legal process. Then if a minor violates the law, the thing that must be done is to give sanctions so that the child can realize that the actions he has done are wrong and can cause violations of the law. The involvement of minors in narcotics is punishable with a crime based on the Narcotics Law "No. 35 of 2009", in which case minors are entitled to legal protection under the Criminal Code and Law "No. 11 of 2012". Where a child will get a dry punishment that is returned to his parents or six months of job training at the Lampung Provincial Social Service